Effects of a high-protein corn coproduct as a replacement for soybean meal in calf starter feed in the postweaning period - R.G. Skinner; W.E. Brown (Journal of Dairy Science)
ABSTRACT: Substitution of soybean meal with dried distillers grains in calf starter feeds (SF) suppresses ADG and feed efficiency. Through the use of fractionation technologies, the ethanol industry is able to produce high-protein corn coproducts (HPCC), which are greater in protein and contain less fiber than traditional distillers grains, and more closely resemble the chemical composition of soybean meal. To evaluate the suitability of an HPCC as a substitute for soybean meal in calf grain, 21 male and 21 female Holstein calves were blocked by sex and birthdate, and randomly assigned to 1 of 3 calf grain treatments, which were offered beginning at 14 d of age. Calf grain treatments were formulated for 0% (CTRL), 50% (50HPCC), or 100% (100HPCC) replacement of the soybean meal (16.6% of diet DM) by HPCC. Rumen-protected Met and Lys were supplemented to meet estimated requirements. Calves were individually housed, and during the data collection period, which occurred after weaning (56–84 d of age), assigned grain was the only feed offered. Dry matter intake was recorded daily, and growth and blood samples were obtained every 14 ± 1 d. Fecal samples were collected on the last 4 d of trial to determine apparent total-tract digestibility. Data were analyzed using PROC MIXED in SAS (v. 9.4) for fixed effects of treatment, sex, and week, when applicable. Preplanned contrasts were used. Treatment, sex, and week interacted on grain intake, whereby 100HPCC males increased DMI more rapidly than males on other treatments but within females only CTRL and 50HPCC increased DMI. Increasing HPCC inclusion linearly increased BW and ADG. Treatment and sex interacted on feed efficiency, whereby 100HPCC males were more efficient than 100HPCC females. Wither height was affected quadratically, as 50HPCC calves were shorter than 100HPCC calves. Inclusion of HPCC increased calf plasma insulin concentration both linearly and compared with CTRL, but contrasts were not detected for blood BHB, BUN, glucose, free fatty acid, or triglyceride concentrations. Apparent total-tract digestibility of DM and CP in diets containing HPCC tended to be greater than CTRL. Overall results indicate the HPCC can replace soybean meal in SF when balanced for the limiting AA Met and Lys.